2004
DOI: 10.1105/tpc.020040
|View full text |Cite
|
Sign up to set email alerts
|

The Melampsora lini AvrL567 Avirulence Genes Are Expressed in Haustoria and Their Products Are Recognized inside Plant Cells

Abstract: The Linum usitatissimum (flax) L gene alleles, which encode nucleotide binding site-Leu rich repeat class intracellular receptor proteins, confer resistance against the Melampsora lini (flax rust) fungus. At least 11 different L resistance specificities are known, and the corresponding avirulence genes in M. lini map to eight independent loci, some of which are complex and encode multiple specificities. We identified an M. lini cDNA marker that cosegregates in an F2 rust family with a complex locus determining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
301
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(309 citation statements)
references
References 84 publications
8
301
0
Order By: Relevance
“…Most recently, similar experiments with Avr proteins from Flor's flax rust pathogen have revealed that these are also detected from inside plant cells (Dodds et al, 2004), indicating that at least some fungal pathogens also translocate Avr/virulence proteins across host cell membranes. This latter work is particularly noteworthy, because coexpression of the flax NB-LRR protein L6 and the fungal Avr protein AvrL567 in tobacco (Nicotiana tabacum) induced an HR-like response, while expression of either protein alone did not.…”
Section: Molecular Analyses Of Plant R Genesmentioning
confidence: 83%
“…Most recently, similar experiments with Avr proteins from Flor's flax rust pathogen have revealed that these are also detected from inside plant cells (Dodds et al, 2004), indicating that at least some fungal pathogens also translocate Avr/virulence proteins across host cell membranes. This latter work is particularly noteworthy, because coexpression of the flax NB-LRR protein L6 and the fungal Avr protein AvrL567 in tobacco (Nicotiana tabacum) induced an HR-like response, while expression of either protein alone did not.…”
Section: Molecular Analyses Of Plant R Genesmentioning
confidence: 83%
“…On the basis of their obligatory and specific association with host plants, aphids would be expected to have a large number of effectors with subtle effects. 46 It is possible, however, that some salivary proteins could be produced in other organs. Hemolymph is constantly pumped in the salivary glands and it is likely that other biological molecules including proteins produced in other tissues make their way into the Figure 5.…”
Section: ' Discussionmentioning
confidence: 99%
“…Different pea aphid clones elicit variable plant wound responses and R-gene resistance is known to be clone-specific 13,45,46 and perhaps linked to clone-specific salivary elicitors. An additional problem with combining transcriptomic and proteomic data sets relates to the wellcharacterized differences that exist in the expression levels between the two systems.…”
Section: ' Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these well-characterized biotrophic pathogens are: ( i ) Puccinia monoica [23] which, similar to aster yellows phytoplasma [24], can induce floral mimicry in order to promote its own sexual reproduction; ( ii ) Melampsora lini [25], which produces effector proteins in haustoria that are recognized inside the plant cell [26]; and ( iii ) Cladosporium fulvum , the tomato pathogen which, during infection, secretes the chitin-binding virulence factor Avr4 that is thought to protect the fungal chitin cell wall from hydrolysis by plant produced chitinases [27]. Extensive studies with P. graminis f. sp.…”
Section: Introductionmentioning
confidence: 99%